Odoo 14 Development Cookbook : Rapidly build, customize, and manage secure and efficient business apps using Odoo's latest features, 4th Edition /: Rapidly build, customize, and manage secure and efficient business apps using Odoo's latest features, 4th Edition. (2020) - Gajjar, Parth; Fayolle, Alexandre; Brunn, Holger; Reis, Daniel
No abstract available